The first registration of the wintering of invasive species of coccinellid Harmonia axyridis (Pallas, 1773) in the bee hives in Belarus - Kruglova, Oksana Yu.; Prischepchik, Oleg V. (Experimental Biology and Biotechnology, 2020)
The first registration in Belarus of an invasive species of coccinellid Harmonia axyridis wintering in bee hives in the Galik village (Drogichinsky district, Brest region) has been established. Some structural features of the obtained sample of H. axyridis are analyzed. The sex ratio is closed to the theoretically expected (1 : 1) – 50.5 % of females and 49.5 % of males. Three of the four main phenotypic color classes of elytra are distinguished in imago – succinea, conspicua and spectabilis. The succinea phenotype is dominated with a frequency of 95.78 %. The elite crest was absent in 10 % of specimens.
Keywords: Harmonia axyridis; wintering; bee hives; invasive species; polymorphism; phenotype